Incidence of inpatient mortality in the palliative medicine unit at tertiary care hospital in Saudi Arabia - Dr. Muna Alshehabi, Dr. Ahmed Salah Ali, Amani Alzayer, (Journal of Medical Biomedical and Applied Sciences, 2016)
After one year of the official opening of the hospital as a tertiary care facility mainly managing cancer patients in the Eastern province in Saudi Arabia IN 2006, a palliative care service has been established as a section under medical oncology department to serve patients at King Fahad Specialist Hospital in Dammam, Saudi Arabia.